BENTUK PENYAJIAN GONDANG DUA DAN ONANG-ONANG (ENDE-ENDE) DALAM MENGIRINGI TOR-TOR PADA UPACARA PERKAWINAN ADAT DI SILAPING KECAMATAN RANAH BATAHAN KABUPATEN PASAMAN BARAT - Niki Adian Nita; Syeilendra Syeilendra; Syahrel Syahrel (SENDRATASIK UNP, 2014)
Abstrak Tor-tor was firstly introduced by the ancestors from North Sumatera. It consisted of three main parts which were the dance called Tor-tor Dance, the music for accompanyiang the dance called as Gondang Dua and the song called as Onang-onang (Ende-ende). In the wedding ceremony, there were four kinds of Tor-tori performed: Tor-tor Raja-raja/Namora mora, Andorsoayu, Naposo/Nauli Bulung and Tor-tor Pengantin. Tor-tor was commonly performed in the afternoon (in the closing stage of a tradisional wedding ceremony). Gondang Dua and Onang-onang (Ende-ende) wich accompanied Tor-tor dance in a wedding party were presented in the formn of dance and music show in Alaman Nabolak (a large yard).   Kata Kunci: Tor-tor Art, Silaping, kecamatan Ranah Batahan Kabupaten Pasaman Barat